Ultrasensitive Lateral Flow Immunoassay of Fluoroquinolone Antibiotic Gatifloxacin Using Au@Ag Nanoparticles as a Signal-Enhancing Label - Olga D. Hendrickson; Nadezhda A. Byzova; Vasily G. Panferov; Elena A. Zvereva; Shen Xing; Anatoly V. Zherdev; Juewen Liu; Hongtao Lei; Boris B. Dzantiev (Biosensors)
Gatifloxacin (GAT), an antibiotic belonging to the fluoroquinolone (FQ) class, is a toxicant that may contaminate food products. In this study, a method of ultrasensitive immunochromatographic detection of GAT was developed for the first time. An indirect format of the lateral flow immunoassay (LFIA) was performed. GAT-specific monoclonal antibodies and labeled anti-species antibodies were used in the LFIA. Bimetallic core@shell Au@Ag nanoparticles (Au@Ag NPs) were synthesized as a new label. Peroxidase-mimic properties of Au@Ag NPs allowed for the catalytic enhancement of the signal on test strips, increasing the assay sensitivity. A mechanism of Au@Ag NPs-mediated catalysis was deduced. Signal amplification was achieved through the oxidative etching of Au@Ag NPs by hydrogen peroxide. This resulted in the formation of gold nanoparticles and Ag+ ions, which catalyzed the oxidation of the peroxidase substrate. Such “chemical enhancement” allowed for reaching the instrumental limit of detection (LOD, calculated by Three Sigma approach) and cutoff of 0.8 and 20 pg/mL, respectively. The enhanced assay procedure can be completed in 21 min. The enhanced LFIA was tested for GAT detection in raw meat samples, and the recoveries from meat were 78.1–114.8%. This method can be recommended as a promising instrument for the sensitive detection of various toxicants.